Effect of a square tunnel on ground responses during earthquakes - Suteja, Kevin (2018)
This project uses PLAXIS 2D to analyse the effect of a square tunnel on ground responses under the earthquake loading. Various dimensions of the soil model will be tested to obtain the horizontal Peak Ground Acceleration (PGA), in which the dimension corresponding to the most critical result will be used for the subsequent analysis. The critical result means the highest value of horizontal PGA, peak velocity and peak displacement obtained from the analysis which corresponds to the likelihood of failures to occur. In addition, different tunnel sizes will be evaluated and location of the tunnel within the soil will be varied by offsetting it from the centreline and the base to identify other possible critical results in the simulation. A subsoil model of 240 m in width and 30 m in height is adopted throughout the analyses. The seismic input for this study includes an earthquake acceleration data. Firstly, to determine the critical tunnel size, three sizes of square tunnel of 3 m, 4 m and 5 m in width are used and evaluated. Subsequently, the governing tunnel size is used for the next analysis. Next, the simulation involves three soil models with different locations of the tunnel, which is located at the depth of 7.5 m, 15 m, and 22.5 m from the ground level. Lastly, the model is constructed with different locations of the tunnel along the same elevation level, by offsetting it from the centreline to four different locations of 0 m, 40 m, 60 m, and 80 m. Comparing all the results from the analyses, it is shown that the bigger the tunnel size, the higher the horizontal PGA and it is also found that the deeper the tunnel is located, the greater the horizontal PGA value is. Through all these simulations, it is also found that the point in which it produces the critical value is always some distance away from the location of the tunnel instead of right above it.